Influência do material restaurador, lesão cervical e tipo de carregamento no comportamento biomecânico de pré-molar superior - Pereira, Fabrícia Araújo (2012)
To evaluate the influence of restorative materials in the presence of cervical lesions on stress distribution and strain pattern of endodontic treated maxillary pre-molars by means 3D-Finite Element Analysis (FEA) and strain gauge test. For finite element analysis, 12 virtual 3D models of maxillary premolar were generated on Rhinoceros software, with MOD cavities and endodontic treatment: A (MOD amalgam restoration), R (MOD composite resin restoration), AL (MOD amalgam restoration + cervical lesion), RL (MOD composite resin restoration + cervical lesion), ALR (MOD amalgam restoration + cervical lesion with composite resin restoration) and RLR (MOD resin composite restoration + cervical lesion with composite resin restoration), each model subjected to two loads in long axis (axial load) and Oblique axis (oblique load). The models were analyzed with finite element software, using the von Mises and Max principal criteria for stress distribution analysis. For the strain gauge test, 14 maxillary premolars were selected, divided into 2 groups (n=7) and sequentially received the following treatments: 1) Endodontic treatment, 2) MOD preparation, 3) restoration with composite resin MOD preparation for the first group and amalgam restoration in the second group, 4) preparation in the cervical and 5) composite resin restoration in cervical region. Two strain gauges were fixed on the buccal and mesial face of each specimen. The specimens were submitted to continuous axial compression loading at a speed of 0.5 mm/min, using a 4,5mm sphere, to a maximum limit of 100 N in a universal testing machine, this loading was applied in long axis touching the buccal and palatal cusps and another loading in oblique touching the buccal cusp Total strain values were obtained by combining the buccal and mesial strain values. These values were analysed using non-parametric test Mann-Whitney and Kruskal-Wallis test (p<.05). The group A showed significantly higher stress concentration and strain values than the R. AL and RL showed higher values of stress and strain when compared with A and ALR, R RLR, respectively, for both types of contact. ALR and RLR had the distribution pattern of stress-strain similar to A and R, respectively. OA, R, AL, RL, RLR ALR showed higher values of stress and strain when subjected to oblique load. MOD cavity restored with amalgam had a higher stress concentration and higher values of strain in premolars endodontically treated. The presence of cervical lesion increased the stress and strain values for premolars restored with MOD amalgam and resin. The cervical lesion restored with composite resin recovered the biomechanical behavior similar to that of samples without lesion. And with the oblique load both restorative materials, the presence of lesion and restored lesion, was a factor modulating the distribution pattern of stress-strain, increasing its values.